1997
DOI: 10.1111/j.1530-0277.1997.tb04481.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Free‐Choice Ethanol Acceptance between Taste Aversion‐Prone and Taste Aversion‐Resistant Rats

Abstract: Taste aversion (TA)-prone (TAP) and TA-resistant (TAR) rats were tested for naive, nonforced acceptance of ethanol. Ethanol acceptance had played no role in line development. Rather, the lines had been developed via bidirectional, nonsibling matings based on susceptibility to develop cyclophosphamide-induced conditioned TAs to a 0.1% saccharin solution (at cyclophosphamide doses of 12.5 mg/kg for males and 15.0 mg/kg for females, i.p.). Rats from the 23rd selectively bred generations, with no prior exposure to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…It has been suggested that the amount of alcohol that rodents will voluntarily consume may be regulated by a general, innate propensity to develop CTA. This hypothesis is supported by results of studies that have shown rats selectively bred for high CTA (taste aversion-prone rats) to the emetic agent, cyclophosphamide, demonstrate greater CTA to a wide variety of pharmacological agents, including alcohol (Elkins et al, 1992), and demonstrate decreased consumption and preference for alcohol than do their counterparts selectively bred for low CTA (taste aversionresistant rats) (Orr et al, 1997). Notably, these lines do not differ in other learning tasks that involve a motivational component, which indicates that the line differences in CTA sensitivity are not due to differences in general learning ability (Elkins, 1986;Hobbs and Elkins, 1983;Hobbs et al, 1993).…”
Section: Discussionmentioning
confidence: 82%
“…It has been suggested that the amount of alcohol that rodents will voluntarily consume may be regulated by a general, innate propensity to develop CTA. This hypothesis is supported by results of studies that have shown rats selectively bred for high CTA (taste aversion-prone rats) to the emetic agent, cyclophosphamide, demonstrate greater CTA to a wide variety of pharmacological agents, including alcohol (Elkins et al, 1992), and demonstrate decreased consumption and preference for alcohol than do their counterparts selectively bred for low CTA (taste aversionresistant rats) (Orr et al, 1997). Notably, these lines do not differ in other learning tasks that involve a motivational component, which indicates that the line differences in CTA sensitivity are not due to differences in general learning ability (Elkins, 1986;Hobbs and Elkins, 1983;Hobbs et al, 1993).…”
Section: Discussionmentioning
confidence: 82%
“…Elkins et al (1992) observed that the selectively bred taste aversion prone (TAP) rats displayed a stronger ethanol-induced CTA response than taste aversion resistant (TAR) rats, despite the fact that ethanol CTA response was not a condition for selection. The TAP and TAR lines display similar abilities in other general learning paradigms, such as radial arm maze and bar pressing for food (Hobbs et al 1993;Orr et al 1997Orr et al , 2004.…”
Section: Discussionmentioning
confidence: 96%
“…Although strain/age differences in general aversion sensitivity and learning capabilities cannot be ruled out as alternative explanations for the results obtained in this study, both aversion sensitivity and ability to form associations presumably could both influence ethanol consumption, either independently of, or in addition to, variations in ethanol sensitivity. For example, in addition to differing in drug-induced CTA, the TAR and TAP rat lines have been shown to differ in ethanol consumption, with TAP rats consuming less ethanol than TAR rats (Orr et al 1997;2004). This suggests that a general proneness (or resistance) to CTA can influence not only ethanol-induced CTA (Elkins et al 1992), but also ethanol consumption.…”
Section: Discussionmentioning
confidence: 99%
“…However, if ethanol contributes to its own self-administration by augmenting the release of mesolimbic dopamine and subsequently stimulating D 2 receptors, then by removing them, the incentive to drink may be lost. Low ethanol preference is correlated with high cyclophosphamide-and ethanol-induced taste aversion 44,45 . Given that the D 2 receptor knockouts avoided ethanol, we speculate that normally the D 2 receptor is involved in both ethanol's positive and negative hedonic effects.…”
Section: Discussionmentioning
confidence: 98%